KUANTIFIKASI DAMPAK PANDEMI COVID-19 TERHADAP INDUSTRI PENYEDIAAN AKOMODASI DI PROVINSI BALI - Dariwardani, Ni Made Inna (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2023)
UNWTO (2020) stated that the Covid-19 pandemic was the biggest crisis in the modern tourism industry. Areas with a high dependency on the tourism sector, such as Bali, since the more profound impact of this crisis. This study intends to quantify the pandemic's impact on industries closely related to tourism and the accommodation industry (i.e., star hotels, non-star hotels/hostels/villas/guest houses/home stays/cottages/other accommodation businesses). Using descriptive statistical analysis, the study examines the pandemic's impact on Bali's accommodation industry in terms of the number of businesses, employment, and the value added /output it produces compared to the pre-pandemic period (2019). From the analysis results, it was found that, in the two years of the pandemic, the accommodation industry in Bali experienced a decline in the number of businesses by almost a quarter for both star and non-star hotels. In terms of employment, almost a quarter of the workers in the accommodation industry lost their job, either becoming unemployed or moving to other business fields in 2020. Meanwhile, the value-added loss of the accommodation industry in Bali is estimated at 18.62 Trillion Rupiah during this pandemic.